1999
DOI: 10.1002/(sici)1521-3803(19991001)43:5<320::aid-food320>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of ‘Azizi’ green pickled olives as affected by alkali process

Abstract: This work was carried out to study the effect of lye treatment at different concentrations (1.0, 2.0 and 2.5%) on some physical-chemical changes of green table olive 'Azizi' cultivar during fermentation process. Results indicated that lye treatment at 1% and 2% using sodium hydroxide were the more suitable concentration for processing green table olive 'Azizi' cultivar under Egyptian condition, where the quality in texture, colour, flavour and appearance was recorded. Statistical analysis revealed that there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The energy of the treatment increases with the lye concentration and room temperature. Strong treatments lead to a higher permeability of the skin (El-Makhzangy Abdel-Rhman, 1999). The penetration of the lye into the flesh is considered sufficient when the chemical reaches about 2/3 of the distance from the exterior to the pit.…”
Section: Packingmentioning
confidence: 99%
“…The energy of the treatment increases with the lye concentration and room temperature. Strong treatments lead to a higher permeability of the skin (El-Makhzangy Abdel-Rhman, 1999). The penetration of the lye into the flesh is considered sufficient when the chemical reaches about 2/3 of the distance from the exterior to the pit.…”
Section: Packingmentioning
confidence: 99%
“…Studies have shown the effect of brine and lye treatment on the chemistry of cell wall7–11 and the texture of olive fruits 12–15. Investigation of the mechanical properties of the olive fruit further to heat treatment has also been carried out 16.…”
Section: Introductionmentioning
confidence: 99%
“…It was clear that penetration in the Ladoelia cultivar was faster than in the Gordal cultivar. The penetration ratio to the pit depends on cell wall composition (Borbolla and Alcala 1981), processing temperature, lye concentration and the polyphenol content of the cultivar itself (El‐Makhzangy and Abdel‐Rahman 1999). It seems also from Table 1 that there is positive correlation between fruit firmness and penetration ratio.…”
Section: Resultsmentioning
confidence: 99%